Sistem Give and Get dalam Perspektif Fikih Muamalah - Khaerul Aqbar; Muhammad Akram Puang Endek; Azwar Azwar (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2023)
This research aims to determine the give and get negotiation system in buying and selling and its laws based on the muamalah fiqh perspective. The type of research used in this research is library research, with a juridical/normative approach. The research results show that the give and get negotiation system in buying and selling is a bargaining method that uses two transaction tricks, namely: 1) adding conditions; and 2) additional prizes/bonuses. In view of muamalah jurisprudence, the give and get negotiation system is permissible. Judging from the side/trick of adding conditions, this is considered permissible because it does not affect the validity of the contract and is not part of the three limiting conditions that damage the contract, such as if the conditions cancel the main purpose of the transaction, the existence of other contracts outside of buying and selling and the contract being dependent on something. which is not certain what happened. Meanwhile, looking at the aspect/trick of adding prizes/bonuses, this is deemed permissible, if it is appropriate and does not conflict with sharia rules. For example, the prizes given do not contain elements of gambling, they are not given by lottery where customers have to pay and then the money is collected and used as prizes, the prizes given must be halal and in accordance with what was promised, and the aim of consumers is to buy goods because they really need them.